The effectiveness of export incentives in revitalising business competitiveness in an organisation:a case study of the Zimbabwe tourism industry - Makanjera, Prince Tapiwa (Midlands State University, 2017)
The research was conducted to establish the effectiveness of export incentives in revitalising business competitiveness in an organisation (A case study of the Zimbabwe tourism industry). It was conducted after the researcher noticed the decline in competitiveness in the tourism industry which was mainly due to the 2014-2015 Ebola crisis, deterioration of major Zimbabwean manufacturing industries which were providing raw material inputs to the industry as well as the banning of importation of certain goods and services by the Zimbabwean government. As a result, the objective of the study was to ascertain whether export incentives led to boost in performance currently being obtained after incorporating a number of incentive schemes. The study adopted a descriptive research design which used questionnaires and interview guides to solicit information from targeted respondents. The study was delimited to the companies and players in the Zimbabwe tourism industry. 7 representative companies were chosen using judgemental sampling and a sample of 49 participants took place in the study. Pearson’s coefficient of correlation was also used as a basis for regression to find the relationship between cumulative growth in export incentive schemes (independent variable) and profits (dependant variable). Results obtained denoted a significant strong positive correlation with the value for R being 0.8852 meaning export incentives where effective in revitalising business competitiveness in the Zimbabwe tourism industry. Based on the research results, the government should continue expanding the scope of export incentives and also enhancing their quality so that they are easily accessible and known.